Sensory trick phenomenon improves motor control in pianists with dystonia: prognostic value of glove-effect - Paulig, Jakobine; Jabusch, Hans-Christian; Großbach, Michael; Boullet, Laurent; Altenmüller, Eckart (Frontiers in Psychology, 2014)
Musician’s dystonia (MD) is a task-specific movement disorder that causes loss of voluntary motor control while playing the instrument. A subgroup of patients displays the so-called sensory trick: alteration of somatosensory input, e.g., by wearing a latex glove, may result in short-term improvement of motor control. In this study, the glove-effect in pianists with MD was quantified and its potential association with MD-severity and outcome after treatment was investigated. Thirty affected pianists were included in the study. Music instrument digital interface-based scale analysis was used for assessment of fine motor control. Therapeutic options included botulinum toxin, pedagogical retraining and anticholinergic medication (trihexyphenidyl). 19% of patients showed significant improvement of fine motor control through wearing a glove. After treatment, outcome was significantly better in patients with a significant pre-treatment sensory trick. We conclude that the sensory trick may have a prognostic value for the outcome after treatment in pianists with MD.